2017
DOI: 10.1126/science.aan2255
|View full text |Cite
|
Sign up to set email alerts
|

Direct atomic-level insight into the active sites of a high-performance PGM-free ORR catalyst

Abstract: Platinum group metal-free (PGM-free) metal-nitrogen-carbon catalysts have emerged as a promising alternative to their costly platinum (Pt)-based counterparts in polymer electrolyte fuel cells (PEFCs) but still face some major challenges, including (i) the identification of the most relevant catalytic site for the oxygen reduction reaction (ORR) and (ii) demonstration of competitive PEFC performance under automotive-application conditions in the hydrogen (H)-air fuel cell. Herein, we demonstrate H-air performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
1,157
4
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,425 publications
(1,207 citation statements)
references
References 44 publications
43
1,157
4
3
Order By: Relevance
“…Recently, Zelenay et al [104] reported a direct observation of FeN 4 moiety with aberration-corrected scanning transmission electron microscopy and high-resolution electron energy loss spectroscopy (EELS) (Fig. 10a, Fig.…”
Section: Structure Of Active Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Zelenay et al [104] reported a direct observation of FeN 4 moiety with aberration-corrected scanning transmission electron microscopy and high-resolution electron energy loss spectroscopy (EELS) (Fig. 10a, Fig.…”
Section: Structure Of Active Sitementioning
confidence: 99%
“…9 Illumination of active sites in carbon-based catalysts 2) in a few-layer graphene sheet. [104]. b EEL spectra of the N K-edge (N k ) and Fe L-edge (Fe L ) acquired from single atoms (1 and 2) and few-layer graphene (3), demonstrate the presence of N around Fe atoms.…”
Section: Structure Of Active Sitementioning
confidence: 99%
“…Figure 1 shows the most commonly proposed active sites in ORR catalysts. One particularly convincing model involves a catalytic center based on metal-N coordination, which was proposed based on experimental evidence from time-of-flight secondary ion mass spectrometry (TOF-SIMS), high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM), and extended X-ray absorption fine structure (EXAFS) [12][13][14]. Simultaneously, metal-free N-doped carbon species with pyridinic and graphitic nitrogen have also been suggested to be responsible for the observed ORR activity based on experimental [15][16][17] and theoretical studies [18][19][20].…”
Section: Orr Reaction Scheme and Active Sites Over Npm Catalystsmentioning
confidence: 99%
“…6 Aniline was employed together with cyanamide (CM) as the N and C sources. Fe precursor was added at the same step of dissolution of aniline and CM.…”
Section: -2mentioning
confidence: 99%